Development of human-supporting hardware and software with limited capabilities - Polvonov Kholbek Nematovich (Genius Journals, 2024)
This article details a smart staff created with high accuracy, and this staff will help the blind easily move safely from one place to another. Software will be installed on the blind support hardware and Raspberry Pi available in our republic. The device uses an ultrasound sensor to determine the barrier distance to the user. The device under study has a USB-camera module, this module announces a pre-existing risk in the program. The images presented on the USB-camera hardware only work when the device is present in its operating activities. It can detect an existing barrier, sending a voice message using a touch sensor included in the program with this accuracy. Warns the user between two and three meters away. By announcing the main content of the project that is being researched, weaning the way of life of representatives of the blind class with limited opportunities. The hardware used the Python programming language. This device is considered an electronic device, and the battery included in it is supplied with Oracle electricity
Keywords: Smart cane; Raspberry PI; Microcontroller; Ultrasonic sensor